A qualitative study of community perceptions and practices relating to blood donation in Cameroon - Solange Dabou; Wilfred Ngwa; Ngo Valery Ngo; Constantine T Asahngwa; Ghyslaine Bruna Djeunang Dongho; Regina Sinsai; Evrard Kepgang; Odette D Kibu; Ronald Mbua Gobina; Denis Alemka Foretia (BMJ Global Health)
Introduction Blood and blood products are essential for patients in need of transfusion therapy, especially those undergoing surgical procedures, childbirth and other injuries. In Cameroon, there is an annual deficit of over 270 000 pints of blood, with a coverage rate of only 17%. This qualitative study investigates the barriers and motivators to blood donation among Cameroonian adults, with the aim of better understanding community perceptions and practices.Methods This ethnographic study was performed using a purposive sampling strategy. Focus group discussions and in-depth interviews were conducted with community members to understand perceptions and practices that serve as motivators and deterrents to blood donation in Yaoundé, Cameroon. Data were transcribed verbatim and analysed thematically to identify emerging themes.Results A total of 25 Cameroonian adults were interviewed. Some participants believed that donating blood is: (1) a humanitarian and life-saving gesture, (2) an act of social and religious responsibility and (3) a means for donors to access health services. Some people do not want to donate blood due to: (1) fear of needles, donor-site pain or possible ritualistic use of donated blood, (2) certain religious beliefs, such as those held by Jehovah’s Witnesses, (3) local and cultural beliefs, (4) the perception that blood donation is a commercial activity for many health personnel and (5) lack of transparency from health personnel. The practice of free and voluntary donation, as well as donations specifically to family and friends, was common. Occasionally, requests for financial remuneration prior to blood donation also emerged.Conclusions Community members displayed both favourable and unfavourable perceptions as well as both safe and risky practices related to blood donation. The positive aspects highlighted the potential for creating a supportive environment for blood donation, while the negative aspects presented the significant challenges facing the development of high-quality blood donation and transfusion services. Efforts to reduce apathy toward blood donation and expand the pool of regular, repeat donors must carefully address the diverse perceptions and practices identified in this study.